Antibiotic Therapy of Mild Community-Acquired Pneumonia in Inpatients - O. V. Molchanova; S. SH. Suleimanov; A. B. Ostrovsky (Антибиотики и Химиотерапия)
From the clinicoeconomic viewpoints the treatment of community-acquired pneumonia in patients without risk factors under hospital conditions with aminopenicillins was more appropriate, whereas for the treatment of patients with risk factors the following scheme of antibiotic therapy was advantageous: a beta-lactam (cefotaxime/ceftriaxone) in combination with a macrolide (azithromycin). The recommended therapy provided statistically lower percentage of negative pneumonia processes and decreased the treatment expenditures.